2011
DOI: 10.1111/j.1476-8070.2011.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Students' Self‐Efficacy for Communication

Abstract: Design students are asked to regularly communicate their ideas to a diverse audience. Students' abilities may be affected by their perceived selfefficacy, the perception of abilities to perform a task. Because self-efficacy is conceived of as context-specific, it is vital to consider self-efficacy as it specifically relates to design studios and the communication within that context, rather than to look at generalised self-efficacy for communication. To that end, this article explains the development and valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Researchers have investigated the impact of the studio critique on self‐efficacy or ‘belief in one's capabilities to organise and execute the courses of action required to produce given attainments’ (Bandura , 3). Studies have shown that communication competence is positively correlated with critique self‐efficacy (Gaffney ) and that self‐efficacy is in turn positively correlated with specific communication instruction (Gaffney ). These findings are supported in related design literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have investigated the impact of the studio critique on self‐efficacy or ‘belief in one's capabilities to organise and execute the courses of action required to produce given attainments’ (Bandura , 3). Studies have shown that communication competence is positively correlated with critique self‐efficacy (Gaffney ) and that self‐efficacy is in turn positively correlated with specific communication instruction (Gaffney ). These findings are supported in related design literature.…”
Section: Resultsmentioning
confidence: 99%
“…Performance criteria specific to design content are also present, but not as prevalent in the literature. Based on the hypothesis that oral communication competence is positively correlated with design critique self-efficacy, Gaffney (2011) utilised measures grounded in prior research (Dannels et al 2008) and established through content validity checks to assess this relationship. Measures for self-efficacy in communication of design studies (graphic, industrial, interior architecture and art) were articulated in terms of behaviours specific to design studio critique.…”
Section: Elements Of An Effective Oral Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples provided by Salas [20] is that a teacher may have a strong sense of self-efficacy in teaching mathematics, but weaker self-efficacy in teaching English; or a student may have high self-efficacy when performing mathematics skills, but a low self-efficacy in language arts. Self-efficacy is related to perceived specific abilities rather than generalized self-beliefs [25]. Bursal and Yigit [26] (2012) proposed that self-efficacy beliefs should be extended to specific subject areas since they are context and subject matter dependent.…”
Section: Self-efficacymentioning
confidence: 99%
“…Barrett (2000) and Percy (2004) cite frustration, alienation, and lack of student participation as outcomes of the traditional design critique. Further research yields a list of factors that may impede student learning, including the size (Blair, 2006) and dynamics of the group (Gray, 2013); language and cultural competencies (Lasserre, 2010;Wong 2011); and perceived self-efficacy (Gaffney, 2011). …”
Section: The Design Critiquementioning
confidence: 99%